Dysregulated high-density lipoprotein and low-density lipoprotein subfractions increase metabolic dysfunction-associated steatotic liver disease risk: a study of patients across body mass index categories - Yu, Hao-Yun; Zhang, Jia-Qi; Sun, Pei-Qi; Li, Qing-Hua; Lin, Hong; Wang, Jia-Yang; Qian, Xiao-Jing; Yang, Xiao-Di; Hu, Cheng; Tian, Ping; Jiang, Yuan-Ye; Lin, Guo-Qiang (Frontiers in Nutrition, 2026)
BackgroundTo investigate biomarker differences among patients with metabolic dysfunction-associated steatotic liver disease (MASLD) across body mass index (BMI) types, we analyzed clinical data from 2,013 subjects and serum samples from 402 patients. The clinical characteristics and lipoprotein subclass profiles were evaluated.MethodsParticipants were grouped based on BMI into overweight MASLD (113 participants), overweight controls (107 participants), lean MASLD (83 participants), and lean controls (99 participants). Serum samples from each group underwent nuclear magnetic resonance-based metabolomic analyses, and clinical and omics data were compared between the lean and overweight MASLD groups and paired control cohorts.ResultsOur study demonstrated distinct omics characteristics for lean MASLD compared with their overweight equivalents. Metabolomic analysis of the serum from the four groups identified six lipoprotein subclasses with significant diagnostic accuracy (area under the curve (AUC) > 0.7), unique to lean individuals with MASLD. In contrast, overweight patients with MASLD had 13 unique lipoprotein subclasses that exhibited a high diagnostic value. These lipoproteins correlate with clinical parameters, such as uric acid, urea, creatinine, eosinophils, blood glucose, and alanine aminotransferase.ConclusionLean and overweight patients with MASLD display unique lipoprotein omics characteristics in an Asian population, primarily involving high-density lipoprotein (HDL) and low-density lipoprotein (LDL) subcomponents, suggesting their potential as effective biomarkers.